Nanoscale dispersion of carbon nanotubes in copper matrix nanocomposites for thermal management applications - ., Ali Samer Muhsan, Faiz Ahmad, Norani M Mohamed, M Rafi Raza (2013)
Uniform dispersion of carbon nanotubes (CNTs) in metal composites has been by far the most significant challenge in the field of CNT-reinforced metal matrices. This work presents a new dispersion and fabrication technique of Carbon nanotubes (CNTs) reinforced copper (Cu) matrix nanocomposites. A combination of nanoscale dispersion of functionalized CNTs in low viscose media of dissolved paraffin wax under ultrasonication treatment followed by powder injection molding (PIM) technique was adopted. CNTs contents were varied from 0 to 10 vol.%. TEM, EDX, FESEM and Raman spectroscopy analysis were used for materials characterization. Information about the degree of purification and functionalization processes, evidences on the existence of the functional groups, effects of ultrasonication time on the treated CNTs, and microstructural analysis of the fabricated Cu/CNTs nanocomposites were determined. The results showed that the impurities of the pristine CNTs such as Fe, Ni catalyst and the amorphous carbon have been significantly removed after purification process. Meanwhile, FESEM and TEM observations showed high stability of CNTs at elevated temperatures. It also showed an excellent homogeneous dispersion of CNTs in Cu matrix and led to a strong interfacial bonding between Cu particles and individual CNTs.